“Improving Students’ Writing Skill Through Think Pair Share Technique at the Second Grade of Mts Al-Khoirot Karangsuko” - Etty Pujawanti (Graduate Program, University of Islam Malang, 2021)
Think Pair Share is a cooperative eruditeness that may influence the students’ handwriting talent buttoned up thought union and distribution There in represent cognate the researcher tries to distinguish if or not the Think Pair Share Technique as a teaching handwriting displays a good resolution on students’ handwriting ableness of Mts Al-Khoirot Karangsuko. So this cognate is conducted to know the effectiveness of Think Pair Share in teaching handwriting in club to aid the pupils meliorate their handwriting talent and besides mightiness consecrate the donation for the teachers in designing the appropriate and effective commandment method dealing with the subject or material they learn.This cognate exploited observational search designing in the manakin of non-randomized with dissimilar treatment of behaviour towards of two dissimilar classes, as they were already unionised good in class. For the aim of assembling facts 44 pupils were participated therein cognate In line with that the researcher victimised backhand essayer to be the instrumentate The experimental course was activated or taught by victimisationing TPS method The control course was not treated by using TPS technique. Than, the test was also apt to both observational and control course The researcher use SPSS_20 to count t-test and cognition the substantial departure between the signify account of the observational and control course.Supported on the data psychoanalysis the significant editorial esteem of t-test was 0. 000 it was less than 0. 05, it indicated that the resolution of t-test psychoanalysis was significant. Moreover, the results but add to make pupils became also eager and active doing the eruditeness cognitive process This was besides big the evidence that for this search the implementation of Think Pair Share technique was an effective commandment technique to help school teacher in achieving the end of commandment eruditeness cognitive process exceptionally in commandment handwriting So it indicated that the aught possibility (Ho) was spurned and alternate possibility (Ha) was recognised.Keyword: Implementation, Think Pair Share technique, Teaching Writing, Writing Skill